Senegal River Valley people living abroad help development back home - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
These days men who have emigrated to Europe are no longer content simply to send money back home to their native villages in Africa. They undertake development projects which help to change the structure of society in their native land. More than 60...